Liquid-liquid extraction of Co(II) from nitrate solution using TOA. (2020) - Mohanty, Archita; Devi, Niharbala; Sukla, Lala Behari; Swain, Nandita
Abstract: Cobalt has widespread industrial applications but if present in excess amounts it may cause several noxious effects. Liquid-liquid extraction process can be useful in cleaning the environment from harmful chemical pollutants. Solvent extraction of cobalt using cobalt nitrate as the feed solution and trioctylamine (TOA) as the extractant in toluene was carried out where the effects of nitric acid concentration, equilibration time, concentration of the extractant and cobalt ions had been investigated. The percentage extraction of Co(II) decreased upon increasing the concentration of acid. A time of 15 min was needed to achieve the extraction equilibrium. Highest percentage extraction of cobalt was achieved using 0.1 M TOA which is 99%. Cobalt loading increased with increase in metal ion concentration. Presence of nitrate ions had almost no significance in the extraction process. The loaded organic phase was stripped using different stripping agents and 99.15% back extraction was achieved with 0.1 mol/L (NH4 )2 CO3 . The extraction mechanism was proposed from the FTIR and slope measurement.